2022
DOI: 10.32604/cmc.2022.019048
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Machine Learning Methods in Modeling Specific Heat Capacity of Nanofluids

Abstract: Nanofluids are extensively applied in various heat transfer mediums for improving their heat transfer characteristics and hence their performance. Specific heat capacity of nanofluids, as one of the thermophysical properties, performs principal role in heat transfer of thermal mediums utilizing nanofluids. In this regard, different studies have been carried out to investigate the influential factors on nanofluids specific heat. Moreover, several regression models based on correlations or artificial intelligenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Their proposed GA-based SVR prediction model beat the MLP in calculating cpNF with higher accuracy than the MLP prediction model. Assad et al [33] reviewed the influence of different parameters in cpNF. They found that properties of solid structures, concentration (wt.%) and temperature have the considerable influence in cpNF [33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their proposed GA-based SVR prediction model beat the MLP in calculating cpNF with higher accuracy than the MLP prediction model. Assad et al [33] reviewed the influence of different parameters in cpNF. They found that properties of solid structures, concentration (wt.%) and temperature have the considerable influence in cpNF [33].…”
Section: Introductionmentioning
confidence: 99%
“…Assad et al [33] reviewed the influence of different parameters in cpNF. They found that properties of solid structures, concentration (wt.%) and temperature have the considerable influence in cpNF [33]. Zobeiry et al [34] used MLP to solve the heat transfer equation in engineering applications and advanced manufacturing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation